An Investigation Of The Performance Of Great Eastern Life Assurance (Malaysia) Berhad - Wing, Cheong Yew (2009)
This research focuses on its three main channels of distribution that offers insurance products and services capable to penetrate to the ever-changing economic environment. It will also give us an insight as to how Great Eastern contributes to the economic activities in so far the insurance is concerned.